2020
DOI: 10.1029/2020tc006063
|View full text |Cite
|
Sign up to set email alerts
|

Microcontinents and Continental Fragments Associated With Subduction Systems

Abstract: Microcontinents and continental fragments are small pieces of continental crust that are surrounded by oceanic lithosphere. Although classically associated with passive margin formation, here we present several preserved microcontinents and continental fragments associated with subduction systems. They are located in the Coral Sea, South China Sea, central Mediterranean and Scotia Sea regions, and a “proto‐microcontinent,” in the Gulf of California. Reviewing the tectonic history of each region and interpretin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 145 publications
(265 reference statements)
0
3
0
Order By: Relevance
“…Obviously, the tectonic evolution of the ABB has resulted in the splitting of an initially Greater Alboran block into several pieces that were first formed during the southward rollback of the slab (Figures 12a and 12b) and then reworked and fragmented again during the westward rollback phase (Figures 12c and 12d). This process is interpreted to be linked with rapid changes in complex subduction dynamics (van den Broek & Gaina, 2020). That is exactly the situation in the present case study at 16‐15 Ma, at the moment when the Balearic slab began to tear bilaterally to the west and southeast (Figures 12b and 12c), thus triggering dispersal of small continental fragments and significant stretching of the GALB by a fast westward rollback (Figures 12c and 12d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the tectonic evolution of the ABB has resulted in the splitting of an initially Greater Alboran block into several pieces that were first formed during the southward rollback of the slab (Figures 12a and 12b) and then reworked and fragmented again during the westward rollback phase (Figures 12c and 12d). This process is interpreted to be linked with rapid changes in complex subduction dynamics (van den Broek & Gaina, 2020). That is exactly the situation in the present case study at 16‐15 Ma, at the moment when the Balearic slab began to tear bilaterally to the west and southeast (Figures 12b and 12c), thus triggering dispersal of small continental fragments and significant stretching of the GALB by a fast westward rollback (Figures 12c and 12d).…”
Section: Discussionmentioning
confidence: 99%
“…The process of slab segmentation and tearing, as proposed in recent geodynamic models of the western Mediterranean Sea (van Hinsbergen et al., 2014; 2020), offers the most likely mechanism to explain the two last stages of opening of the Algero‐Balearic domain. The EABB case study illustrates how collision‐induced rotations following slab rollback and the associated increase of arc curvature may lead to complex back‐arc rifting systems with highly variable geometry and strain rates and may foster fore‐arc fragmentation in a short geological time scale (van den Broek & Gaina, 2020; van Hinsbergen et al., 2020; Guillaume et al., 2010; Wallace et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We envisage that a variety of other tectonically driven isolation processes (e.g., rifting to isolate the plate) may also lead to formation of new CLM. Van den Broek & Gaina (2020) suggested that extension and rifting play an important role in the formation of microcontinents, and proposed southern Baja California to be a “proto‐microcontinent”. Here, we provide evidence for such a process on the Baja California margin.…”
Section: Discussionmentioning
confidence: 99%